2018
DOI: 10.1186/s12889-018-5175-5
|View full text |Cite
|
Sign up to set email alerts
|

‘This is the beginning of the new me’: process evaluation of a group fitness intervention to promote wellbeing in formerly homeless individuals

Abstract: Group fitness sessions represent a promising intervention to improve wellbeing of this population. However, the need for more personalised care when delivering fitness sessions, due to the complexity of health issues prevalent in this population, was identified. This has implications for already limited resources, including staffing. Strategies to address this are required to ensure the continuity of fitness programs. Impact evaluation to quantify changes/improvements in wellbeing would complement this work an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…Such observations are important to consider when replicating or expanding an intervention, as the personal qualities of those who deliver the intervention can greatly impact on its success, as previous research has demonstrated (Jago et al., 2015; Smith et al., 2017). This observation is also supported by the findings of Sofija and colleagues, as participants in this similar intervention delivered in Australia also placed significant emphasis on the importance of building a good rapport with instructors and having staff who are supportive and non-judgemental (Sofija et al., 2018), a finding that is mirrored in this present study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Such observations are important to consider when replicating or expanding an intervention, as the personal qualities of those who deliver the intervention can greatly impact on its success, as previous research has demonstrated (Jago et al., 2015; Smith et al., 2017). This observation is also supported by the findings of Sofija and colleagues, as participants in this similar intervention delivered in Australia also placed significant emphasis on the importance of building a good rapport with instructors and having staff who are supportive and non-judgemental (Sofija et al., 2018), a finding that is mirrored in this present study.…”
Section: Discussionsupporting
confidence: 88%
“…A mixed-methods review of health interventions for homeless individuals identified no robust randomized trials which had physical activity as a core component (Coles, Themessl-Huber, & Freeman, 2012), and only one qualitative study in which peer-led education was utilized. A recent process evaluation by Sofija, Plugge, Wiseman, and Harris (2018) found that formerly homeless individuals experienced improvements to their overall wellbeing and social inclusion through participation in a group exercise intervention (Sofija et al., 2018). Similarly, Welty Peachey, Lyras, Borland, and & Cohen (2013) evaluation of the street soccer USA cup concluded that the intervention was positively perceived by participants as it created a sense of community and an inclusive environment for social interaction to occur (Welty Peachey et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In their pilot life skills program with young people experiencing homelessness, Sisselman-Borgia [19] found that participants noted relationships with program facilitators and mentors as extremely influential and impactful on their development through the program. Similarly, Sofija et al [46] highlighted the importance of facilitators on participants' wellbeing in a group fitness intervention with adults who had experienced homelessness. Rapport development and satisfaction of basic psychological needs were core components of MST4Life™'s delivery style [11,15] and aligned with PYD principles in promoting opportunities to build positive relationships with adults and peers [3].…”
Section: Discussionmentioning
confidence: 99%
“…Social networks have also been related to the higher or lower risk for alcohol and other drugs consumption and have been the object of interventions that improve readiness to change the use of alcohol and other drugs and abstinence self-efficacy (Kennedy et al, 2017). Finally, social support has been promoted through physical activity; fitness interventions in the framework of supporting housing facilities (Sofija et al, 2018) and running groups for homeless women (Dawes et al, 2019) showed benefits both for physical and mental wellbeing and for social inclusion.…”
Section: Introductionmentioning
confidence: 99%